Exploring the Relationship between the Factors Affecting Consumer Behavior concerning Mobile Phones in Nepal - Rai, Arjun; Bhattarai, Mandip (Dristikon: A Multidisciplinary Journal, 2023)
This study examined the relationship between publicity, company website, advertisement, brand ambassador, friends' recommendations, and social media while making buying decisions by consumers concerning mobile phone purchases. The population of the study comprised university students of Nepal. A structured questionnaire was sent to respondents. Out of the returned responses, 165 responses were selected for this study. A correlation test was employed to examine the relationship between the stated variables of the study. The finding demonstrated positive correlations between the variables of the test. All the variables had a statistically positive correlation with each other at <.001, except (friends' recommendation and company website; and friend recommendation and brand ambassador).